Eco-profile approach in watershed and river basin management for addressing water rights and conflicts at micro scale - Damasco, Mavhaire; S, Rajendrakumar; N, Tharanidevi; S, Shimly; Rahut, Dil Bahadur; Timilsina, Raja Rajendra (Frontiers in Water, 2025)
Eco-profile studies help in continuous assessment and monitoring of river basin functions; the planners, and decision-makers deploy study findings to address problems associated within river basins. In this paper, we reviewed the study covering the eco-profile based watershed and river basin management practices and the benefits of eco-profile in understanding and addressing water-related issues at the micro-level. The study uses a systematic literature review approach called the PRISMA framework (Preferred Reporting Items for Systematic reviews and Meta-Analyses) to collect and process the literature. Our study found that eco-profile based implementations improves the river basin functions and addresses the micro-level issues related to water rights and conflicts that are usually not addressed during water resources management. Through eco-profile study, the key ecological indicators at micro and macro scales can be identified that help to predict the continuous changes of biotic and abiotic conditions within the watershed and river basin regions. The present study discusses the advantage of eco-profile in the watershed, measures to comprehend river basin function, community role, and approach to solve the water rights and conflicts at the micro scale. The study also recommends the inclusion of eco-profile framework and eco-profile policy in integrated water resources management programs specific to river basin/watershed management activities.